PTIP Inhibits Cell Invasion in Esophageal Squamous Cell Carcinoma via Modulation of EphA2 Expression - Han, Xiao; Zhu, Yaning; Shen, Li; Zhou, Yu; Pang, Liqun; Zhou, Wubi; Gu, Hao; Han, Kairong; Yang, Yijun; Jiang, Chao; Xie, Jun; Zhang, Chengwan; et al. (Frontiers in Oncology, 2021)
Esophageal squamous cell carcinoma (ESCC) is a highly aggressive malignancy and treatment failure is largely due to metastasis and invasion. Aberrant tumor cell adhesion is often associated with tumor progression and metastasis. However, the exact details of cell adhesion in ESCC progression have yet to be determined. In our study, the clinical relevance of Pax2 transactivation domain-interacting protein (PTIP/PAXIP1) was analyzed by immunohistochemistry of ESCC tissues. We found that low expression of PTIP was associated with lymph node metastasis in ESCC, and loss-of-function approaches showed that depletion of PTIP promoted ESCC cell migration and invasion both in vitro and in vivo. Analysis integrating RNA-seq and ChIP-seq data revealed that PTIP directly regulated ephrin type-A receptor 2 (EphA2) expression in ESCC cells. Moreover, PTIP inhibited EphA2 expression by competing with Fosl2, which attenuated the invasion ability of ESCC cells. These results collectively suggest that PTIP regulates ESCC invasion through modulation of EphA2 expression and hence presents a potential therapeutic target for its treatment.